Comparison of a new digital imaging technique for yeast cell counting and viability assessments with traditional methods. Issue 2 (1st April 2015) - Thomson, K.; Bhat, A.; Carvell, J.
Abstract : In this study, a new rapid automated yeast cell counter was assessed. The cell counter (Aber Countstar) uses bright‐field microscopy and a dye‐exclusion method. This study's aim was to determine whether this method could be effectively employed in an automated slide based counter to assess viability and to compare this method with results from traditional microscopy and from a radio‐frequency impedance‐based instrument (Aber Compact Lab Yeast Analyser). Excellent correlations were observed between methods. The instrument performed well over a range of yeast concentrations ( R 2 = 0.9913 correlation between automated and manual live cell concentrations). Cell diameters compared well with manual recordings. The instrument was also able to track decreasing cell viability in conjunction with the haemocytometer at viabilities over 20%. The radio‐frequency impedance based instrument exhibited the smallest deviation between 10 repeats, followed by the cell counter (SD: ± 1.08 × 10 7 ; ± 5.97 × 10 7, respectively). Manual counts using a haemocytometer exhibited the largest error between repeats (SD: ± 2.63 × 10 8 ) and also required substantially more time (2.28 min) compared with the cell counter (7 sec). The automated cell counter successfully reduced inter‐operator errors, a major hindrance with manual analyses. Tests carried out at a brewery in the UK demonstrated that the cell counter provides consistent counts for assorted yeast strains. External tests highlighted the instrument's ease of use and consistency among different strains of brewing yeast and various stages in the brewing process. Copyright © 2015 The Institute of Brewing & Distilling